2018
DOI: 10.1002/etc.4024
|View full text |Cite
|
Sign up to set email alerts
|

Linking in vitro estrogenicity to adverse effects in the inland silverside (Menidia beryllina)

Abstract: High-throughput cell assays that detect and integrate the response of multiple chemicals acting via a common mode of action have the potential to enhance current environmental monitoring practices. Establishing the linkage between in vitro and in vivo responses is key to demonstrating that in vitro cell assays can be predictive of ecologically relevant outcomes. The present study investigated the potency of 17β-estradiol (E2), estrone (E1), nonylphenol (NP), and treated wastewater effluent using the readily av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The CECs may affect specific biological pathways, leading to sublethal effects such as metabolic, immune, and behavioral impairments. A number of studies have demonstrated that CECs can induce molecular changes at concentrations much lower than those eliciting morphological changes (Van den Belt et al 2004; Mehinto et al 2018). Therefore, evaluating standard toxicity endpoints such as growth, survival, and organosomatic indices could underestimate their impact on aquatic health.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CECs may affect specific biological pathways, leading to sublethal effects such as metabolic, immune, and behavioral impairments. A number of studies have demonstrated that CECs can induce molecular changes at concentrations much lower than those eliciting morphological changes (Van den Belt et al 2004; Mehinto et al 2018). Therefore, evaluating standard toxicity endpoints such as growth, survival, and organosomatic indices could underestimate their impact on aquatic health.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other studies that reported estrogenic effects at concentrations found in the positive control (Shappell et al 2010). Previous research has documented the linkage among occurrence of estrogens, in vitro ERα bioactivity, and in vivo fish responses (Van den Belt et al 2004; Dobbins et al 2008; Mehinto et al 2018). These studies showed that in vitro bioassays and gene biomarkers are typically more sensitive than organismal responses, highlighting the value of a tiered effects–based monitoring strategy as an early warning tool.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have recently served as a useful euryhaline model for the study of endocrine disruption and other categories of sub-lethal effects in the Bay−Delta and beyond(Brander et al 2013;Brander et al 2016a;DeCourten and Brander 2017;Mehinto et al 2018). M. beryllina are part of the EPA's Whole Effluent Toxicity (WET) Testing Program (NPDES WET;…”
mentioning
confidence: 99%